Analiza sekwencji kodującej eksonu III genu CYP1B1 w polskiej populacji pacjentów chorych na jaskrę wrodzoną i młodzieńczą - Koraszewska-Matuszewska, Bronisława; Samochowiec-Donocik, Elżbieta; Zielińska, Aleksandra; Kruszyński, Piotr; Wąsik, Tomasz J. (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
Several mutations of CYP1B1 gene, a member of cytochrome P450 gene family, have been associated with occurrence of primary congenital glaucoma. The aim of presented work was to investigate CYP1B1 gene exon III mutations in 72 unrelated Polish patients with primary congenital glaucoma (C), juvenile glaucoma (J) and juvenile glaucoma suspects (P). In one patient we have detected homozygous duplication of 10bp at nucleotide 8046 resulting in synthesis of truncated protein, first found among the polish population. Furthermore, sequence analysis revealed three distinct single nucleotide polymorphisms at nucleotides 8131 (C→G), 8184 (C→T) and 8195 (A→G,) in examined populations. The haplotypes in homozygous state (C/C/A, C/C/G, and G/T/A) were present in 52.6% cases. Since it is suggested that the presence of these haplotypes may be linked to mutations in exon II of the CYP1B1 gene, we plan to analyze that exon in the future.